INVITRO RELEASE COMPARISON OF NIFEDIPINE FROM MARKETED AND PREPARED CONTROLLED RELEASE FORMULATIONS BY MATHEMATICAL MODELING - ASHWINI DESHPANDE; SHIRISH DESHPANDE; HUSSAIN LOKHANDWALA (International Journal of Pharma and Bio Sciences, 2013)
The objectives of this study were (a) To Perform in-vitro release study of marketed Nifedipine formulation,(b) To check effect of integrity on release profiles, (c) To determine the possibility of switchover from one formulation to another formulation and (d) To compare release profiles with formulated batches by application of mathematical models. Four marketed and two prepared controlled release (CR) products of Nifedipine were used in the study. Different release kinetic models were applied to drug release data in order to predict release mechanisms and kinetics. A criterion for choosing the most appropriate model was goodness of fit based on R2, Akaike Information Criteria (AIC) and Model selection criteria (MSC). Marked differences in dissolution characteristics of preparations of halved tablets were observed as compare to intact tablets. Mathematical modeling and kinetics of drug release results depicted that the switchover from the product to other is not advisable for the dosage forms under study.